Legal uncertainty as a means of competition limitation in the sphere of state and municipal purchases - A. I. Sidorenko (Russian Journal of Economics and Law, 2014)
Objective: to show the means of legal uncertainty creating based on the drawbacks of legislation at the stage of applying for auctions for state and municipal purchases, and to propose ways to solve the stated problem by changing the existing legal regulation. Methods: common dialectical-materialistic method, allow in to reveal the interdependence of the discretion of authorities when distributing the budget; the methods of analysis, induction, comparison and statistics. Results: legislation provisions are shown, which ensure the methods of making the state order market close for entrepreneurs deprived from illegal distribution of the budget; proposals for the legislation changing are formulated. Scientific novelty: The means of creating unequal conditions for the state and municipal purchases are defined (as revelation of corruptive factors of the legislation on public auctions), as well as the measures for their elimination. Practical value: proposals are formulated for improving the existing legal regulation.